2020
DOI: 10.1186/s40981-020-00378-9
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vein thrombosis and cerebral infarction after video-assisted thoracic surgery of the left upper lobe: a case series

Abstract: Background Pulmonary vein thrombosis (PVT) and cerebral infarction are rare but critical complications after video-assisted thoracic surgery (VATS). Case presentation We experienced two cases of massive middle cerebral artery infarction after VATS for the left upper lobe. Although the precise source of their embolus was never identified, both cases were clinically suspected PVT. Unfortunately, case 2 died because of progressive cerebral herniation. We decided to perform contrast-enhanced computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Anticoagulation may be recommended in an individual basis given those contradictory findings regarding the occurrence of cerebral infarction after PVST [16]. In addition, previous studies reported the use of several different anticoagulants including warfarin or dabigatran for the management of PVST, but there are yet no preferred duration or modality of anticoagulation [1,9,12]. Low-molecular-weight heparin (LMWH) treatment is associated with enhanced activity of the fibrinolytic system [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anticoagulation may be recommended in an individual basis given those contradictory findings regarding the occurrence of cerebral infarction after PVST [16]. In addition, previous studies reported the use of several different anticoagulants including warfarin or dabigatran for the management of PVST, but there are yet no preferred duration or modality of anticoagulation [1,9,12]. Low-molecular-weight heparin (LMWH) treatment is associated with enhanced activity of the fibrinolytic system [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Left upper lobectomy and left pneumonectomy are suggested to be the independent risk factors for the development of early postoperative stroke [18]. However, whether PVST is the direct cause of postoperative cerebral infarction is not yet clear [12,20]. No patient experienced systemic embolism (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thrombosis at the pulmonary vein transection site reportedly occurs in 11.7-30.8% of patients undergoing left upper lobectomy [1,3,4]. Care must be taken because cerebral infarction is relatively frequently reported after left upper lobectomy [4,5], and left pneumonectomy and left upper lobectomy are considered independent risk factors for postoperative stroke [6].…”
Section: Discussionmentioning
confidence: 99%
“…Thoracoscopic lobectomy is beneficial in many aspects, while postoperative complications may still occur to varying degrees. Venous thromboembolism (VTE) is a serious complication after thoracoscopic lobectomy, 8 , 9 and patients with thrombosis are at high risk of critical symptoms including pulmonary embolism, infarction, or chronic thromboembolic pulmonary hypertension. As a case report presented, a patient with LC who underwent right lower lobectomy and mediastinal lymphadenectomy developed thrombosis in the right lower lobar pulmonary artery stump three months later.…”
Section: Introductionmentioning
confidence: 99%